PENGARUH PENGETAHUAN DAN SIKAP PERAWAT TERHADAP KESELAMATAN PASIEN: LITERATURE REVIEW - Rezky Pratama; Stefano Geraldi; Niko Sudibjo (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2021)
Patient safety is defined as the prevention of harm to patients while in health care. Patientsafety also means reducing the risk of unnecessary harm when the patient is in healthnursing care. Patients need maximum protection guarantees in health services. It is veryimportant to evaluate the knowledge and attitudes of nurses about patient safety throughthe identification of all risks that may be faced by nurses. Given the importance of patientsafety, the purpose of this study was to examine the effect of nurses' knowledge andattitudes on patient safety. The method used in writing this article is in the form of aliterature review. Article searches are carried out through Google Search Engine throughthe use of the keywords “patient safety”, “knowledge”, “attitude” and “nurse”. The workunit, and knowledge of patient safety are factors that are significantly related to knowledgeof patient safety. In addition, gender, work experience, having patient safety information,knowledge about patient safety have a significant relationship with attitudes towardspatient safety. Nurses can be more confident in increasing knowledge and attitudestowards patient safety through a good understanding of the factors that influence eachother. A high attitude towards patient safety can help nurses to continue to provide safepatient care